A longitudinal case study of curriculum-based L2 writing development. (February 2021) - Maxim, Hiram H.
Abstract: In light of the long-term support needed for L2 writing development (Byrnes et al., 2010), this chapter presents a multi-year longitudinal case study of three L2 learners who completed three consecutive instructional levels of German in an articulated undergraduate program at a U.S. university. The article begins by contextualizing the study in terms of the SFL-informed literacy-oriented curriculum, wherein writing development is driven by the use of sequenced genre-based writing tasks throughout the four-year program. Next, a triangulated analysis is conducted of the three learners' performances on these writing tasks according to (a) traditional syntactic complexity variables (e.g., mean length of sentence; mean length of clause); (b) SFL-based measures of learners' emergent meaning-making (e.g., transitivity development; taxis; thematization patterns); and (c) learner interviews. Individual differences and similarities across curricular levels are reported and also correlated with a larger cohort who completed the same tasks ( n = 117). Emphasis is placed on the varied development within an articulated program of study that has clear goals for learners' writing performance across the curriculum. Learners' reactions to the genre-based pedagogy and curricular sequencing are also presented. Last, implications of these findings for building models of collegiate L2 writing instruction are discussed.